2004
DOI: 10.1071/rd02104
|View full text |Cite
|
Sign up to set email alerts
|

Parallel changes between the percentage of fetal pituitary cells immunoreactive to oestrogen receptor α and the concentration of 17β-oestradiol in fetal and maternal plasma during gestation in sheep

Abstract: The present study was designed to investigate the relationship between fetal sheep pituitary oestrogen receptor (ER) alpha expression and changes in fetal and maternal plasma 17beta-oestradiol (E2) concentrations during gestation. The results revealed that immunoreactivity for ER was located in the nuclei and distributed throughout the fetal pituitary gland during gestation. The percentage of ERalpha-positive cells was approximately 2% of the total cell population in female fetuses at Day 60 of gestation, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…The present results showed that AR-ir cells were observed throughout anterior pituitary at day 60 of gestation, the earliest stage examined. But only a few ER -ir cells were located in a small region at the base of the anterior pituitary and in a band immediately adjacent to the neurointermediate lobe (Sheng et al 1998;Cui et al 2004). This indicates that AR emerges in anterior pituitary before day 60 of gestation, and AR expression in anterior pituitary occurs earlier than ER .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present results showed that AR-ir cells were observed throughout anterior pituitary at day 60 of gestation, the earliest stage examined. But only a few ER -ir cells were located in a small region at the base of the anterior pituitary and in a band immediately adjacent to the neurointermediate lobe (Sheng et al 1998;Cui et al 2004). This indicates that AR emerges in anterior pituitary before day 60 of gestation, and AR expression in anterior pituitary occurs earlier than ER .…”
Section: Discussionmentioning
confidence: 99%
“…For AR and ER double staining, ER monoclonal antibody (NCL-ER-LH2, Novocastra, Newcastle upon Tyne, UK) was used, which has been previously utilized to determine the expression of ER in sheep (Sheng et al 1998;Cui et al 2004;Tian et al 2004). AR staining was Wrstly performed as described for AR and pituitary hormone double staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…The ontogeny and cellular distribution of ER expression in the pituitary gland have been extensively studied in developing mammalian fetuses, such as in rat (Pasqualini et al 1999;Nishihara et al 2000), sheep (Sheng et al 1998;Cui et al 2004), and human (Brandenberger et al 1997). ER expression in these species can be detected at early stages of fetal development, rise to a maximum around the middle of gestation, and then decline at birth (Sheng et al 1998;Cui et al 2004).…”
Section: Introductionmentioning
confidence: 98%